2015
DOI: 10.1002/cncr.29857
|View full text |Cite
|
Sign up to set email alerts
|

Radiation modality use and cardiopulmonary mortality risk in elderly patients with esophageal cancer

Abstract: BACKGROUND It is currently unclear if the superior normal organ sparing effect of Intensity Modulated Radiation Therapy (IMRT) as compared to three-dimensional radiation therapy (3D) has clinical impact on survival and cardiopulmonary mortality in esophageal cancer (EC) patients. METHODS We identified 2,553 patients older than age 65 years from the SEER/Texas Cancer Registry-Medicare databases who had non-metastatic EC diagnosed between 2002 and 2009 and were treated with either 3D (n=2,240) or IMRT (n=313) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 26 publications
2
40
1
Order By: Relevance
“…For the models determined by the SVSS algorithm, patients who received IMRT had significantly reduced risks of pericardial and pleural effusion as well as death before effusion type. This agrees with results from several previous studies which showed that IMRT increased patient survival compared to 3D-CRT [22] [23]. …”
Section: Discussionsupporting
confidence: 93%
“…For the models determined by the SVSS algorithm, patients who received IMRT had significantly reduced risks of pericardial and pleural effusion as well as death before effusion type. This agrees with results from several previous studies which showed that IMRT increased patient survival compared to 3D-CRT [22] [23]. …”
Section: Discussionsupporting
confidence: 93%
“…However, even RT alone requires special attention in aged patients. The use of intensity-modulated RT was shown to be associated with significantly lower rates of all-cause mortality, cardiac mortality, and other-cause mortality in patients with esophageal cancer (11). Such new technology might be able to reduce deaths from other causes in aged patients.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for IMRT in reducing toxicities over 3DCRT comes from an analysis of two large cancer registries, encompassing over 2500 elderly patients [32]. Of note, IMRT had increased over 10-fold from 2002 to 2009, with a corresponding decrease in 3DCRT.…”
Section: Intensity-modulated Radiotherapymentioning
confidence: 99%